Pengaruh Mediasi Dalam Penyelesaian Sengketa Waris - Khozanah Ilma Terok; Zaini Munawir; Anggreni Atmei Lubis (JUNCTO: Jurnal Ilmiah Hukum, 2021)
Mediation in the process of proceedings at the Court is an important stage, so the Judge can delay the proceedings. At the first session, the Judge was obliged to encourage the parties to carry out the mediation process and provide explanations to the parties regarding the procedures and costs of mediation. This is important so that the parties can know the mechanisms, procedures and costs of mediation that must be issued in the mediation process. The mediation process is divided into three stages, namely the pre-mediation stage, the stage of mediation implementation, and the final stage of the implementation of the mediation results. The mediation stage begins with important steps: preliminary remarks by the mediator, presentation and presentation of the parties' stories, sorting and clarifying issues, discussing and negotiating agreed issues, creating options, finding points of agreement and formulating decisions, recording and retelling decisions and closing mediation. Effect of the mediation process in resolving inheritance disputes in Decision No.2570 / Pdt.G / 2017 / PA. Mdn can be said to be successful, because the parties to the dispute can reconcile according to the peace deeds made and agreed by each party in litigation. Constraints faced in the mediation process in resolving disputes over the distribution of shared assets after divorce, namely the absence of a mechanism that can force one party or parties to attend mediation meetings, lack of goodwill of the parties to reconcile.